.NET Gadgeteer: A Platform for Custom Devices - Villar, Nicolas; Scott, James; Hodges, Steve; Hammil, Kerry; Miller, Colin (Proceedings of Pervasive 2012, 2012)
.NET Gadgeteer is a new platform conceived to make it easier to design and build custom electronic devices and systems for a range of ubiquitous and mobile computing scenarios. It consists of three main elements: solder-less modular electronic hardware; object-oriented managed software libraries accessed using a high-level programming language and established development environment; and 3D design and construction tools designed to facilitate a great deal of control over the form factor of the resulting electronic devices. Each of these elements is designed to be accessible to a wide range of people with varying backgrounds and levels of experience and at the same time provide enough flexibility to allow experts to build relatively sophisticated devices and complex systems in less time than they are used to. In this paper we describe the .NET Gadgeteer system in detail for the first time, explaining a number of key design decisions and reporting on its use by new users and experts alike.